CD26-inhibition correlates with the absence of chronic lung allograft dysfunction and decreases fibroblast activity in vitro. (1st June 2022) - Moneke, I; Ögütür, E; Chatterjee, S; Haberecker, M; Jang, J H; Fähndrich, S; Senbaklavaci, Ö; Faccioli, E; Opitz, I; Passlick, B; Diederichs, S; Jungraithmayr, W
Abstract: Objective: Chronic lung allograft dysfunction (CLAD) limits the survival after lung transplantation (Tx). CLAD is characterized by progressive fibrosis of small airways and lung parenchyma. No effective therapy is available that reverses or prevents CLAD. CD26 is a molecule with enzymatic activity also playing a key role in the progression of fibrotic diseases. Here, we analyzed the inhibitory effect of CD26 on fibroblast activity in vitro and the role of CD26-inhibition on allograft rejection in lung transplant patients. Methods: Profibrogenic mRNA and protein levels were analyzed in vitro on the CD26-expressing fibroblast cell line Wi-38 using RT-qPCR and Western blot. CD26 was inhibited by Vildagliptin. Migration and proliferation activity of activated fibroblasts were analyzed by Incucyte® and Celltiter-Glo®. Characteristics of patients undergoing lung Tx between 2004 and 2021 were reviewed. Lung biopsies were analyzed by immunohistochemistry (IHC) for CD26. Results: In vitro, the expression of profibrogenic genes (αSMA, FAPα, IGFBP7, Collagen 3 and Fibronectin) was significantly reduced in activated lung fibroblasts by Vildagliptin treatment. Also, migration and proliferation activity were attenuated by Vildagliptin. In 221 patients analyzed, CLAD was absent in 34 patients treated with the CD26-inhibitor Sitagliptin vs. an incidence of 18% in patients without Sitagliptin intake (p=0.02). Five-year survival in patients on Sitagliptin was significantly improved vs. patients without CD26-inhibitor intake (80% vs. 58%, p=0.006). Likewise, the incidence of acute cellular rejection (ACR) was significantly reduced in patients on Sitagliptin (7% vs. 35%, p=0.01). IHC of patient lung biopsies showed expression of CD26 in perifibrotic areas of CLAD lesions. Additional clinical data from University Hospital Zurich and from University Hospital Padua confirmed the finding that Sitagliptin intake correlated with the absence of acute and chronic allograft rejection. Conclusion: CD26-inhibition attenuates key pro-fibrotic mediators and fibroblast activity in vitro. Impressively, patients on CD26-inhibitor did not show any CLAD. Moreover, ACR was significantly reduced. Gliptins which are in routine clinical use for the treatment of type II diabetes therefore seem to have great potential to be repurposed for a novel clinical application against lung allograft rejection.